2015
DOI: 10.1039/c5cc07056b
|View full text |Cite
|
Sign up to set email alerts
|

Coupled molecular motions driven by light or chemical inputs: spiropyran to merocyanine isomerisation followed by pseudorotaxane formation

Abstract: We have designed and prepared a new dual stimuli-responsive guest molecule containing a spiropyran fragment and a pyridinium moiety. Acid addition or UV-light irradiation induces guest transformation to a merocyanine isomer, promoting the threading motion through a 24-crown-8 macrocycle and the formation of a [2]pseudorotaxane complex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…The Klajn group and the Mukeherjee group reported that positively‐charged coordinated cages can stabilize the merocyanine isomer in water under room light. Crown ether, sulfonatocalixarene, and cucurbit[n]urils show binding preference to the positively charged region of the merocyanine isomer and thus stabilize this isomer. Cyclodextrins and octa acid capsules prefer the neutral spiro isomer.…”
Section: Figurementioning
confidence: 99%
“…The Klajn group and the Mukeherjee group reported that positively‐charged coordinated cages can stabilize the merocyanine isomer in water under room light. Crown ether, sulfonatocalixarene, and cucurbit[n]urils show binding preference to the positively charged region of the merocyanine isomer and thus stabilize this isomer. Cyclodextrins and octa acid capsules prefer the neutral spiro isomer.…”
Section: Figurementioning
confidence: 99%
“…The incorporation of SP switches in guest's scaffolds is widely documented in literature [22,23,24,25] . The main aim of this strategy resides in coupling the isomerization of the switch to the thermodynamic stability of the resulting supramolecular complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of SP switches in guest's scaffolds is widely documented in literature. [ 22 , 23 , 24 , 25 ] The main aim of this strategy resides in coupling the isomerization of the switch to the thermodynamic stability of the resulting supramolecular complexes. In contrast, the number of examples describing the incorporation of SP units into the structures of host molecules is less frequent.…”
Section: Introductionmentioning
confidence: 99%
“…Photochromism – the reversible interconversion of a molecule, with at least one of the reactions being induced by absorption of light, between two forms having different absorption spectra4 – has been thoroughly investigated since the 1980s and become a key component of the supramolecular chemist toolbox. The prominent changes in structure and properties associated with photoisomerization have been exploited to control threading,5 self-assembly processes,6 and non-equilibrium behavior7 in [2]pseudorotaxanes, and molecular movements (shuttling, rotation),8 surface properties,9 catalysis10 and reactivity 11…”
Section: Introductionmentioning
confidence: 99%